2017
DOI: 10.1177/1010428317707374
|View full text |Cite
|
Sign up to set email alerts
|

Biological function of long noncoding RNAsnaRin HER2-positive breast cancer cells

Abstract: Purpose: Long noncoding RNA, snaR (small NF90-associated RNA), has been reported to be upregulated in various cancer cell lines. We evaluated the additional role of snaR in HER2-positive breast cancer cell lines. Methods: We explored changes of expression of snaR among the selected long noncoding RNAs which have a potential in cancer proliferation or progression. The proliferation, migration, and invasion of HER2-positive breast cancer cells (SK-BR3) were evaluated by snaR with RNA interruption in 3-(4,5-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
2
36
3
Order By: Relevance
“…Relative to normal ones, the expression level of SNHG5 was elevated in 30 BRCA tissues and cell lines including MDA-MB-231, MCF7, SKBR3, T47D, BT474 and BT20. [25][26][27] Zahra et al also confirmed that SNHG5 was involved in cancer stage, overall grade, mitotic rate and tumor size in BRCA patients. 28 Notably, SNHG5 was detected to correlate with positive reaction of estrogen receptor, progesterone receptor and Her2/neu expression, 28 which were main subtypes of BRCA patients.…”
Section: Breast Cancer (Brca)mentioning
confidence: 99%
“…Relative to normal ones, the expression level of SNHG5 was elevated in 30 BRCA tissues and cell lines including MDA-MB-231, MCF7, SKBR3, T47D, BT474 and BT20. [25][26][27] Zahra et al also confirmed that SNHG5 was involved in cancer stage, overall grade, mitotic rate and tumor size in BRCA patients. 28 Notably, SNHG5 was detected to correlate with positive reaction of estrogen receptor, progesterone receptor and Her2/neu expression, 28 which were main subtypes of BRCA patients.…”
Section: Breast Cancer (Brca)mentioning
confidence: 99%
“…The ZFAS1 gene is located on chromosome 20 (q13.13) and is transcribed from the antisense strand near the 5′-end of the protein-encoding gene Znfx1 and the hosts three C/D box snoRNAs (Snord12, -12b, and -12c) [10]. Various studies have identified ZFAS1 as a cancer oncogene in: glioma [11,12], gastric cancer [13,14,15,16,17], colorectal cancer [18,19,20,21], hepatocellular carcinoma [22], ovarian cancer [23,24], melanoma [25], non-small cell lung cancer [26], osteosarcoma [27], esophageal squamous cell carcinoma [28], and hematological malignancies [29,30]. However, suppressor roles for ZFAS1 lncRNA in breast cancer and hepatocellular carcinoma have also been reported [12,13,21].…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs are involved in various biological processes, such as cell differentiation and cell cycle control, through transcription, post-transcription, and epigenetic regulation [21]. These RNAs play a role in tumorigenesis and a variety of human malignancies (e.g., papillary thyroid cancer, hepatocellular carcinoma, and breast neoplasms) [21]. The aberrant expression of Aurora kinases can disturb the cell cycle in mitosis and cytokinesis, thereby leading to genetic instability, followed by the stimulation of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the knockdown of HOXA11-AS reportedly inhibits the formation of cell colonies and arrests the cell cycle at G0/G1 phase [22]. Lee et al showed that MER11C, PSF-inhibiting RNA, and SCA8 were also upregulated in the breast cancer cell lines (e.g., SK-BR3) [21].…”
Section: Discussionmentioning
confidence: 99%